Validitas Buku Ensiklopedia Kelas Mamalia Di Kawasan Hutan Mangrove Desa Sungai Bakau Kabupaten Tanah Laut Dalam Melatih Keterampilan Berpikir Kritis Mahasiswa - Salma Ulanhar; Kaspul Kaspul (Wahana-Bio: Jurnal Biologi dan Pembelajarannya, 2026)
This study aims to describe the validity of the Class Encyclopedia of Mammals in the Mangrove Forest Area of Sungai Bakau Village, Tanah Laut Regency as a contextual teaching material to train students' critical thinking skills. The method used is the Educational Design Research (EDR) approach with the Tessmer formative evaluation model at the expert review stage. Validity was assessed by three expert lecturers in Biology Education using an instrument covering aspects of content, language, and presentation. The assessment results showed an average score of 3.61 with a valid category. These findings indicate that the encyclopedia has an appropriate content structure, clear presentation, and is suitable for use as a teaching material in biology learning. Thus, this encyclopedia is declared valid as a learning medium that can support the development of students' contextual-based critical thinking skills.